Semiautomatic Algorithm for 3D Modelling of Finite Elements of the Cochlea. - Castro Egler, Cristina; García-González, Antonio Luis (American Scientific Publishers, 2017)
This paper presents a method of generating a ﬁnite element numerical model of the inner ear of the human auditory system. The method consists of two phases, including a semiautomatic algorithm of image processing, which has been developed to obtain a characteristic-point cloud that deﬁne the cochlea cross sections, vestibule contours and curvilinear path of the semi-circular canals, and modelling of the point cloud to create the numerical model for the ﬁnite element method. The result is a complete numerical inner-ear model composed of a coiled- shaped cochlea with three chambers divided by the basilar membrane and Reissner’s membrane, and it is attached to a model of the vestibule and semi-circular canals through hexahedral ﬁnite elements. Although the numerical model can be improved, this numerical model may provide support for a more complete model that can perform numerical tests with the ﬁnite element method. In the future, the model output may be printed using three-dimensional (3D) technology and biological materials to create an artiﬁcial model with vital functions.
Keywords: Cóclea; Algoritmos; Finite Elements; Inner Ear; 3D Modelling